Blending climate action and rural development in Africa's Sahel - Woomer, P.L.; Roobroeck, D.; Alia, D.Y. (IntechOpen, 2022)
This paper describes the opportunity for combining climate action and improved food and nutritional security as mutual elements of rural development projects, with particular reference to the situation in the African Sahel. This progress is achieved by identifying climate-smart agricultural production technologies and bundling them into solutions for inclusion within larger projects and programs. Seventeen (17) such technologies are offered in this chapter that represent genetic innovations, improved soil and water management, and directed improvement across landscapes. Examples of the efficacy of these technologies are presented based on results from the African Agricultural Transformation Program (TAAT) with specific reference to improved cereal production. An example of the deployment of TAAT technologies for millet and sorghum involving 83,620 households managing 123,863 ha led to nearly 200,000 MT of increased food production worth about $42 million. This effort led to an estimated annual increase of 177,279 MT CO2e in biomass and soil worth $3.9 million, assuming buyers could be found. The relationship between three principal drivers of agricultural transformation, the public, private, and farming sectors, is considered in terms of how these different technologies are mobilized and deployed. The potential for increasing food supply and carbon gains under current agricultural investment levels across the Sahel by International Financial Institutions, about $683 million per year, is described. This chapter then offers recommendations in how improved rural development projects combining climate action and food security in the Sahel may be designed in the future.